Methodology for integrating isometric self-stretching into the structure of manual manipulations - Sheremeta, Taras (Педагогічна Академія: наукові записки, 2025)
Relevance of the study is determined by the need to increase the efficiency of manual manipulations under conditions of growing prevalence of musculoskeletal dysfunctions and occupational overload of practitioners. The aim of the study is to substantiate the methodological foundations for integrating isometric self-stretching into the structure of manual manipulations based on the principles of dynamic stability, biomechanical efficiency, and ergonomically optimized movement organization of the practitioner. Methods. The study employs theoretical analysis and generalization of scientific sources, systemic and biomechanical analysis, and modeling of force transmission processes and movement organization in manual practice. A comparative analysis of isometric self-stretching against passive stretching and post-isometric relaxation was conducted across functional parameters: preservation of therapeutic contact, proprioceptive activation, load redistribution, and impact on practitioner endurance. Results. The biomechanical and functional foundations of manual manipulations were investigated, and the role of isometric self-stretching as an integrated mechanism for maintaining myofascial balance and proprioceptive regulation was established. It was demonstrated that the effectiveness of manual impact increases when displacement of the center of mass, micromovements, and breathing-postural coordination are properly synchronized; the role of intra-abdominal pressure as a structurally necessary stabilizing component during force application was clarified. Key scientific and practical problems were identified: the absence of standardized integration algorithms, disruption of biomechanical coherence, difficulties in controlling proprioceptive processes, and the lack of self-monitoring protocols within the structure of the manual session. A conceptual-applied model of isometric self-stretching integration was developed, ensuring systemic organization of movementthrough a closed regulatory loop and enhancing the stability of therapeutic impact. Conclusions. Integrating isometric self-stretching as a component of dynamic stability improves the stability of therapeutic impact, reduces localized overload, and enhances the ergonomic characteristics of professional activity. The transition from isolated technique application to their systemic integration within a unified biomechanical model has been substantiated. Prospects for further research are associated with the standardization of integration algorithms, development of self-monitoring protocols, quantitative evaluation of the proposed model’s effectiveness, and its adaptation to various fields of physical therapy and sports practice.